Logistics Capability, Information Technology, and Innovation Capability of Logistics Service Providers: Empirical Evidence from East Coast Malaysia - Nur Fadiah Binti Mohd Zawawi; Sazali Abdul Wahab; Abdullah Al Mamun; Ghazali Bin Ahmad; Syed Ali Fazal (International Review of Management and Marketing, 2017)
The growth and transformation of the manufacturing sector all around the world has spurred on the demand for logistics services. These industries need logistics as the mobility medium to run the business process especially for road logistics transportation. The road logistics transportation is a key role to move goods from suppliers to customers in order to complete the logistics cycle. This situation has sparked congestion, which has caused delivery delay and rising costs. These two major effects of congestion have affected the business performance, for either the logistics service providers (LSPs) or the consignees. Thus, the purpose of this paper is to empirically examine the relationships of logistics capability, IT implementation, and innovation capability with the LSPs' performance. Using the correlation and standard multiple regression analysis, the theoretical models and hypotheses in this study are tested based on empirical data gathered from 81 LSPs in the East Coast region registered with the FMM Directory of Malaysian Industries. The results reveal that logistics capability, IT implementation, and innovation capability have significant positive relationships with the LSPs' performance. Among them, innovation capability contributes the most to the logistics performance in the East Coast region. This study has bridged the literature gap by providing empirical evidence and new insights on logistics performance using the Malaysian sample.